Public health and cost consequences of time delays to thrombectomy for acute ischemic stroke. (3rd November 2020) - Kunz, Wolfgang G.; Hunink, Myriam G.; Almekhlafi, Mohammed A.; Menon, Bijoy K.; Saver, Jeffrey L.; Dippel, Diederik W.J.; Majoie, Charles B.L.M.; Jovin, Tudor G.; Davalos, Antoni; Bracard, Serge; Guillemin, Francis; Campbell, Bruce C.V.; et al.
Abstract : Objective: To determine public health and cost consequences of time delays to endovascular thrombectomy (EVT) for patients, health care systems, and society, we estimated quality-adjusted life-years (QALYs) of EVT-treated patients and associated costs based on times to treatment. Methods: The Markov model analysis was performed from US health care and societal perspectives over a lifetime horizon. Contemporary data from 7 trials within the Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials (HERMES) collaboration served as data source. Aside from cumulative lifetime costs, we calculated the net monetary benefit (NMB) to determine the economic value of care. We used a contemporary willingness-to-pay threshold of 100, 000 per QALY for NMB calculations. Results: Every 10 minutes of earlier treatment resulted in an average gain of 39 days (95% prediction interval 23–53 days) of disability-free life. Overall, the cumulative lifetime costs for patients with earlier or later treatment were similar. Patients with later treatment had higher morbidity-related costs but over a shorter time span due to their shorter life expectancy, resulting in similar lifetime costs as in patients with early treatment. Regarding the economic value of care, every 10 minutes of earlier treatment increased the NMB by 10, 593 (95% prediction interval 5, 549–14, 847) and by 10, 915 (95% prediction interval 5, 928–15, 356) taking health care and societal perspectives, respectively. Conclusions: Any time delay to EVT reduces QALYs and decreases the economic value of care provided by this intervention. Health care policies to implement efficient prehospital triage and to accelerate in-hospital workflow are urgently needed.